Evaluating the Effectiveness of School Nursing Program in Promoting Healthy Behaviors Among Elementary School Students - Rawahneh, Niveen Z. AL; Abdelhafez, Amina M.; Lopez, Hilda T.; Conde, Maurine T.; Alababseh, Lujain W. (Journal of Neonatal Surgery, 2025)
School nursing programs are vital because they contribute significantly to student health and well-being by offering direct healthcare services, health education, and early intervention measures within the school context. This study assesses the efficacy of a school nursing intervention in enhancing students' health behaviors. The intervention aimed to promote regular physical exercise, balanced nutrition, appropriate hydration, mental health awareness, and optimal sleep patterns through structured educational sessions and individualized health consultations. The study used a quasi-experimental pre- and post-research design. Data was collected both before and after the intervention to examine changes in students' health-related behaviors. To ensure comparability, schools were chosen based on similar socioeconomic backgrounds. Statistical analyses, including paired t-tests, were performed to assess the significance of changes in key health behaviors, while ANCOVA was used to compensate for potential confounders such as baseline health status, age, and prior health knowledge. The paired-samples t-test demonstrated significant differences between pre- and post-intervention measures in the understanding of students. The study found significant gains (p < 0.05) in all targeted health behaviors, particularly in mental well-being awareness (+30%) and appropriate sleep (+30%). Furthermore, students displayed a stronger understanding of good eating behaviors and physical activity standards following intervention. These findings highlight the importance of the school-based health program in promoting long-term wellness in students. The study advocates for the inclusion of nursing-led health interventions in educational settings to promote preventive healthcare and long-term health improvements in school-aged populations.